2005
DOI: 10.1093/jxb/eri293
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoenolpyruvate carboxykinase and its potential role in the catabolism of organic acids in the flesh of soft fruit during ripening

Abstract: Previous studies of grapes and tomatoes have shown that the abundance of phosphoenolpyruvate carboxykinase (PEPCK) increases in their flesh at the start of ripening, and that this coincides with a decrease in its citrate and/or malate content. Thus, PEPCK might function in the catabolism of organic acid anions during the ripening of these fruits. In the present study, the abundance of PEPCK was determined in the flesh of blueberries, raspberries, red currants, and strawberries at different stages of their deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
62
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 35 publications
6
62
0
Order By: Relevance
“…5, B and C), support this theory (Fig. 7), particularly considering that a role for PEPCK in organic acid catabolism in certain fleshy fruits has been suggested previously during ripening (Famiani et al, 2005).…”
Section: Metabolism During Ripening Of Dixiland Peach Fruit: Preparinsupporting
confidence: 81%
“…5, B and C), support this theory (Fig. 7), particularly considering that a role for PEPCK in organic acid catabolism in certain fleshy fruits has been suggested previously during ripening (Famiani et al, 2005).…”
Section: Metabolism During Ripening Of Dixiland Peach Fruit: Preparinsupporting
confidence: 81%
“…In tomato, PEPCK abundance increases at the start of ripening, during which there is a decrease in malate content (Bahrami et al, 2001). This has led to the suggestion that PEPCK is involved in this dissimilation and that part of this dissimilated malate may be used in gluconeogenesis (Leegood and Walker, 2003;Famiani et al, 2005Famiani et al, , 2009. In contrast, NADP-ME isoforms function in chloroplasts and the cytosol (Drincovich et al, 2001;Gerrard Wheeler et al, 2005) and catalyze the reversible conversion of malate and pyruvate (Farineau, 1977;Drincovich et al, 2001).…”
mentioning
confidence: 99%
“…Given this complexity and the variety of flux modes within carboxylic acid metabolism (Sweetlove et al, 2010), it is not obvious what the best strategy for engineering increased accumulation of carboxylic acids in fleshy fruits would be. This is reflected in the range of enzymes that have been proposed to control fruit citrate accumulation, including phosphoenolpyruvate carboxylase (Guillet et al, 2002), phosphoenolpyruvate carboxykinase (Famiani et al, 2005), citrate synthase (Sadka et al, 2000a), and aconitase (Sadka et al, 2000b; Degu et al, 2011).To identify a suitable metabolic engineering strategy for increasing carboxylic acid content of tomato, we undertook a detailed biochemical study of an introgression line of tomato (Eshed and Zamir, 1995). A specific line with an introgressed segment from Solanum pennellii on chromosome 2 (IL2-5) was identified that showed reproducible increases in citrate and malate during the later stages of fruit development but had minimal changes in gross developmental characteristics such as fruit size and number.…”
mentioning
confidence: 99%
“…Given this complexity and the variety of flux modes within carboxylic acid metabolism (Sweetlove et al, 2010), it is not obvious what the best strategy for engineering increased accumulation of carboxylic acids in fleshy fruits would be. This is reflected in the range of enzymes that have been proposed to control fruit citrate accumulation, including phosphoenolpyruvate carboxylase (Guillet et al, 2002), phosphoenolpyruvate carboxykinase (Famiani et al, 2005), citrate synthase (Sadka et al, 2000a), and aconitase (Sadka et al, 2000b; Degu et al, 2011).…”
mentioning
confidence: 99%